Forest Resource Utilization by the Siberut Community and its Implications for the Siberut Island Biosphere Reserve Policy - Fifin Nopiansyah; Sambas Basuni; Yohanes Purwanto; Nandi Kosmaryandi (Institut Pertanian Bogor (IPB University), 2016)
Siberut is one of the islands in the Mentawai group, located off the West Coast of Sumatera in Indonesia. The community of Siberut is well known for their traditional wisdom in utilizing the forest resources and unique biodiversity of their island home. For this reason, Siberut has been officially declared as biosphere reserve. One of the aims the biosphere reserve concept is to enable traditional communities to use their forest resources in a sustainable manner. Unwise activities in the utilization of forest resources have implications for the whole community and for the management of biosphere reserves. This study aimed to compile and analyse first-hand information about current usage of forest resources on Siberut and to identify particular community behavior having implications for the implementation of the Siberut Island biosphere reserve policy. The study was conducted in 3 villages of Siberut traditional communities in Mentawai Islands Regency, that are Matotonan, Saibi Samukop, and Sagulubbek villages. The study applied a qualitative approach, where data were collected through a study of relevant literatures, interviews, and direct observation. Then the data were analyzed to develop an understanding of the current forest utilization and its implications for the policy in accurately. The results showed that the Siberut traditional communities are still dependent on forest resources, even though their utilization practices have been changing in recent times. For example in this research they adopted some new technologies, which it can be destructive to forest resources in the future. For that reason, the reseach suggest the management of Siberut Island Biosphere Reserve to restore those particular aspects of the traditional wisdom which have beneficial for the sustainability of forest resources utilization. In this case involving of local community starting from centre of planning to implementation process will be benefit for a better management of the reserve.